Aplicação do hipoclorito de sódio na nutrição da soja e do feijão - Silva, José Iran Cardoso da [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
The sodium hypochlorite has been used in agriculture for many producers to control of fungal diseases, however, there are not scientific information related with the plant nutrition. The present work had as objective to evaluate effect of the sodium hypochlorite application in different doses in the fresh and dry biomass and in the macronutrients and micronutrients text in leaf of soybean and bean. The experiments were carried at the greenhouse of the Departamento de Recursos Naturais/Ciência do Solo, FCA/UNESP, Botucatu/SP, in columns of rigid PVC with capacity to 1.0 liter of soil. The soil was classified as typical dystrophic Red Latossol of medium texture. The experimental design used in each experiments was complete randomized, with 4 replications. The treatments in each experiments were constituted of 5 doses of sodium hypochlorite (0.0, 0.5 L ha-1, 1.0 L ha-1, 2.0 L ha-1 and 4.0 L ha-1). The following parameters were evaluated: chemical analysis and electrical conductivity of the soil; fresh and dry biomass aboveground of the plants and macro and micronutrients texts in leaf of the plants. In the present work toxicity symptom was not observed, as for example the appearance of clorose and leaf burning, even when the concentration highest of sodium hypochlorite was used. The doses of sodium hypochlorite tested did not reflect significantly (p > 0.05%) in the weight of fresh and dry biomasses of bean, however, the dry biomass of soybean presented significant difference (p < 0.05%) among the doses of sodium hypochlorite applied through of the leaf. Average texts of macro and micronutrients obtained in leaf of bean were not affected by the doses of sodium hypochlorite studied. In relation to the macro and micronutrient studied in the soybean, only the sulphur and magnesium texts in leaf presented significant difference in function of the application of doses of sodium... (Complete abstract click electronic access below)
Keywords: Hipoclorito de sódio; Soja - Nutrição; Feijão - Nutrição; Sodium hypochlorite